Socio-economic and institutional factors affecting smallholders farmers to adopt agroforestry practices in southern province of Rwanda - Mukundente Liliane; Ndunda Ezekiel; G Gathuru (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
This paper is mainly focused on identifying the socio economic and institutional factors influencing agroforestry adoption in Southern Province. Field survey was conducted during July to September, 2019 using structured questionnaire. This study was carried out in four districts in southern province of Rwanda. The number of respondents involved in the study was 650 farmers. A descriptive survey design was used in this study. For the selection of the sample, the study adopted a stratified random sampling technique and simple random technique. Binary logit regression model has been used to determine the factors affecting farmers adopting agroforestry. Finally, Binary regression analysis showed no significant association between the adoption of agroforestry practices and respondent's age, gender, marital status, farming experience or income range of the respondents. On the other hand, there is a positive significant association between the adoption of agroforestry practices and household size is 0.00 p-value as well as the farm size of the respondents. It is expected that farmers with larger household size are more likely to adopt agroforestry practices than farmers with smaller household size and also shows that most of the farmers who were more likely to adopt agroforestry had a bigger land acreage for planting more trees.